Effects of a Brain-Computer Interface With Virtual Reality (VR) Neurofeedback: A Pilot Study in Chronic Stroke Patients - Vourvopoulos, Athanasios; Pardo, Octavio Marin; Lefebvre, Stéphanie; Neureither, Meghan; Saldana, David; Jahng, Esther; Liew, Sook-Lei (Frontiers in Human Neuroscience, 2019)
Rehabilitation for stroke patients with severe motor impairments is burdensome and demanding because most of the current rehabilitation options require some volitional movement to train the affected side. However, research has shown that survivors of severe stroke may receive modest benefits from action observation, virtual reality (VR), and brain-computer interfaces (BCIs). These approaches have shown some success in strengthening key motor pathways thought to support motor recovery after stroke. The purpose of this study was to combine the principles of action observation, VR, and BCI in a platform called REINVENT and assess its effects on four chronic stroke patients across different levels of motor impairment. REINVENT acquires post-stroke EEG signals that indicate an attempt to move and drives the movement of a virtual avatar arm, allowing patient-driven action observation neurofeedback in VR. In addition, synchronous electromyography (EMG) data were also captured to monitor overt muscle activity. Our results show that this EEG-based BCI can be used by stroke survivors across a wide range of motor disabilities. Finally, individual results suggest that patients with more severe motor impairments benefit the most from EEG-based neurofeedback, while patients with more mild impairments may benefit more from EMG-based feedback, harnessing existing sensorimotor pathways. Future research is needed to confirm these findings in a larger and more diverse population.